Faktor yang Berhubungan dengan Perilaku Petani Padi dalam Penggunaan Pestisida di Desa Muara, Cilamaya Wetan Kabupaten Karawang - Soedradjat, Maryam Sakinah; Afifah, Lutfi Afifah; Sulandjari, Kuswarini Sulandjari (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
Unwise use of pesticides can cause residues that are harmful to human health and have a negative impact on the environment. Factors related to farmers' behavior can be one of the key determinants of how far they understand and implement safe, sustainable pesticide use practices. The study aims to analyze the factors associated with the behavior of peasants in Muara village, Cilamaya Wetan district, Karawang district. Behavior includes knowledge, attitudes, and actions consisting of aspects of pesticide type, dosage, time, spray frequency, self-protection, pesticides application techniques, and compliance with instructions for use. The research was conducted from September to October 2023. Sampling proportionate stratified random sampling obtained 85 respondents. Data collection techniques include observations, tests, questionnaires, and interviews. The study used a survey method using Spearman Rank analysis. Data were analyzed using validity tests, reliability tests, quantitative descriptive analysis, and Spearman Rank correlation tests. The results of the research showed that the factors associated with the behavior of wildfish farmers in the use of pesticides were land area (X3) with a correlation of 0.239, farming experience (X4) with the correlations of 0.258, and perception of pests and plant diseases (X7) with a correlation of 0,233. Whereas education (X1), income (X2), social involvement (X5), as well as the role of the farmer (X6) had no significant correlation with farmers' behaviour in pesticide use.